2005
DOI: 10.1016/j.ijmedinf.2005.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Involving the patient: A prospective study on use, appreciation and effectiveness of an information system in head and neck cancer care

Abstract: The electronic health information support system was used intensively and highly appreciated by H&N cancer patients. The system enabled the early detection of occurring health problems that required direct intervention. ICT can play an additional role in the management of patients, also in a relatively elderly and computer illiterate patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
40
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 21 publications
3
40
2
Order By: Relevance
“…A research group based in the Netherlands developed and tested a comprehensive electronic health information support system for use in head and neck cancer care [27]. The system had four patient-related functions: facilitating communication between patients and healthcare providers; providing information about the disease and its treatment; connecting patients with patients similarly diagnosed; and monitoring patients after hospital discharge.…”
Section: Introductionmentioning
confidence: 99%
“…A research group based in the Netherlands developed and tested a comprehensive electronic health information support system for use in head and neck cancer care [27]. The system had four patient-related functions: facilitating communication between patients and healthcare providers; providing information about the disease and its treatment; connecting patients with patients similarly diagnosed; and monitoring patients after hospital discharge.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, several studies have demonstrated various applications of log file tracking: to assess e-learning,10 – 12 to identify how to support health professionals or lay people,1318 to observe the interest aroused by items of cancer-related public knowledge18 and to support patient information 19 – 21. There are no studies of log file assessment after institutional campaigns, although reference institutions’ websites command more credibility among the lay population as sources of reliable information 22.…”
mentioning
confidence: 99%
“…The first of all was Immunity and Safety data with two sections, Prevention of Disease and Awareness and Knowledge about Disease. Other researcher showed that tele health technologies have been used with good results in areas of preventive care and management of certain disease especially in chronic diseases including osteoarthritis, heart disease and diabetes (42) and also used for consult with patient for health behaviors and give information about disease (43) and patient had satisfaction with these systems (91%) (44) and also have emphasized on improve knowledge with give information about nature, causes, stages, signs and symptoms of disease for self management and better recovery from it (45, 46). These researches have contingency with this results study.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers showed that patient to be inclined to access to rest results (50, 51, 52), monitor chronic disease including asthma, hypertension, congestive heart failure and high risk pregnancy (43) chemotherapy side effects and symptoms of patient receiving chemotherapy (43, 53) and had satisfied with using these systems (94%) (44). The patient had concern about and problem with when they used medical equipment and need to get information about application and some other information about these equipment (54).…”
Section: Discussionmentioning
confidence: 99%